GAMBARAN HASIL PEMERIKSAAN WIDAL MENGGUNAKAN SERUM DAN PLASMA EDTA PADA SUSPEK DEMAM TIFOID DI RUMAH SAKIT UMUM DAHA HUSADA KOTA KEDIRI - Indra Fauzi Sabban Sabban; Erlinda Magdalena; Siska Wardani; Ismiy Wahyuni (Asosiasi Dosen Muda Indonesia, 2023)
Typhoid fever is a systemic infection of the digestive system caused by the bacteria Salmonella typhi and Salmonella paratyphi. This disease is still a major health problem in the world. One of the tests for typhoid fever is the slide method widal test which measures antibodies to Salmonella typhi antigens. The most frequently used specimen is serum, but some hospitals use plasma as a substitute for serum. The purpose of this study was to compare the results of the widal examination using EDTA serum and plasma in suspected typhoid fever at Daha Husada General Hospital, Kediri City. The research design used a comparative study with a total population of 54 people. The study sample consisted of 15 patients using the quota sampling method. Analysis of research data used the Lilliefors test to test data normality and the Wilcoxon test to determine whether there was a comparison of the results of the widal examination using EDTA serum and plasma. The results showed that there were differences in the results of the widal examination using EDTA serum and plasma. The conclusion of the study was that there was a comparison of the results of the widal examination using EDTA serum and plasma in suspected typhoid fever at Daha Husada General Hospital, Kediri City.